Respuesta :
c + (4 - 3c) - 2 = 0
c + 4 - 3c - 2 = 0
c - 3c + 4 - 2 = 0
-2c + 2 = 0
- 2 - 2
-2c = -2
-2 -2
c = 1
c + 4 - 3c - 2 = 0
c - 3c + 4 - 2 = 0
-2c + 2 = 0
- 2 - 2
-2c = -2
-2 -2
c = 1
c+(4−3c)−2=0
simplify step-by-step.
c+4−3c−2=0
c+4+−3c+−2=0
(c+−3c)+(4+−2)=0(Combine Like Terms)
−2c+2=0
−2c+2=0
Subtract 2 from both sides.
−2c+2−2=0−2
−2c=−2
Divide both sides by -2.
−2c/−2 = −2/−2
c=1
simplify step-by-step.
c+4−3c−2=0
c+4+−3c+−2=0
(c+−3c)+(4+−2)=0(Combine Like Terms)
−2c+2=0
−2c+2=0
Subtract 2 from both sides.
−2c+2−2=0−2
−2c=−2
Divide both sides by -2.
−2c/−2 = −2/−2
c=1